Effects of plyometric training on sport-specific tests in female volleyball players - Trajkovic, N.; Kristicevic, T.; Baic, M. (Acta Kinesiologica, 2016)
Vertical jump height has been identified as a critical component in the sport of volleyball. Therefore, improving vertical jump in volleyball should be the main objective for all coaches. The main objective of this study was to determine the effects of plyometric training methods on jumping ability in female junior volleyball players. Sixty female volleyball players (mean ± SD age, 17 ± 6 months) participated in this study. The experimental group conducted six weeks of plyometric training method for developing explosive leg power. Players were tested for Attack and Block jump test with and without approach. There were significant interaction between the groups for right foot block jump and left foot block jump. Plyometric training induced significant improvements in RFBJ (p<0.01), LFBJ, COBJ, SSBJ (p<0.05). However, control group showed no significant improvements (p>0.05) in any Spike and Block jump test. In conclusion, completion of a 6 week plyometric training program improved selected Block jump tests in female junior players. However, there were no significant changes in Attack jumps following the plyometric training program.